Histone deacetylase 1 and 2 differentially regulate apoptosis by opposing effects on extracellular signal-regulated kinase 1/2 - Lei, W-W; Zhang, K-H; Pan, X-C; Wang, D-M; Hu, Y; Yang, Y-N; Song, J-G (Cell death & disease, 2010)
Histone deacetylases (HDACs) are epigenetic regulators that are important for the control of various pathophysiological events. We found that HDAC inhibitors completely abolished transforming growth factor- β 1 (TGF- β 1)-induced apoptosis in AML-12 and primary mouse hepatocytes. Expression of a dominant-negative mutant of HDAC1 or downregulation of HDAC1 by RNAi both suppressed TGF- β 1-induced apoptosis. In addition, overexpression of HDAC1 enhanced TGF- β 1-induced apoptosis, and the rescue of HDAC1 expression in HDAC1 RNAi cells restored the apoptotic response of cells to TGF- β 1. These data indicate that HDAC1 functions as a proapoptotic factor in TGF- β 1-induced apoptosis. In contrast, downregulation of HDAC2 by RNAi increased spontaneous apoptosis and markedly enhanced TGF- β 1-induced apoptosis, suggesting that HDAC2 has a reciprocal role in controlling cell survival. Furthermore, inhibition of extracellular signal-regulated kinase 1/2 (ERK1/2) by MEK1 inhibitor PD98059 or expression of a kinase-dead mutant of MEK1 restored the apoptotic response to TGF- β 1 in HDAC1 RNAi cells. Strikingly, HDAC2 RNAi caused an inhibition of ERK1/2, and the spontaneous apoptosis can be abolished by reactivation of ERK1/2. Taken together, our data demonstrate that HDAC1 and 2 reciprocally affect cell viability by differential regulation of ERK1/2; these observations provide insight into the roles and potential mechanisms of HDAC1 and 2 in apoptosis.